Persepsi Nasabah Terhadap Keputusan Pengambilan Pembiayaan Syariah Pada KSPPS BMT Anfa’ NU Kabupaten Magelang - Nurhakiki nurhakiki; Yeny fitriyani yenyfitriyani; qurotul aini qurotulaini; Muchammad Afiffudin Afiffudin (ITB AAS INDONESIA Surakarta, 2023)
This research empirically tests the influence of customer perceptions on the decision to finance in Islamic banking. The variables used in this study are customer knowledge (X1), service quality (X2), bank reputation (X3), and threshold (X4) as independent variables, and murabahah financing (Y) as the dependent variable. The data used in this study is primary data with data collection methods using questionnaires distributed by KSPPS BMT Anfa' NU where KSPP BMT Anfa' NU is one of the Islamic Microfinance Institutions in Magelang Province. The number of samples that were successfully processed reached 30 respondents. The sampling technique is the accidental sampling technique, namely, selecting samples randomly. Partial t-test and simultaneous f-test were used as data analysis methods. The data were analyzed using the SPSS 21 program. The results of the survey hypothesis test showed that: (1) The variable of customer knowledge influences murabahah financing decisions but is not material. (2) Service quality positively and significantly affects murabahah financing decisions. Murabahah Financing, (3) Bank registration influences the purchase decision of Murabahah Financing but does not have a material impact.